MLKL as an emerging machinery for modulating organelle dynamics: regulatory mechanisms, pathophysiological significance, and targeted therapeutics - Wang, Yang; Wei, Wei; Zhang, Yu; Miao, Jingrong; Bao, Xiaofeng; Lu, Chunfeng (Frontiers in Pharmacology, 2025)
Mixed lineage kinase domain-like protein (MLKL) is a pseudokinase featured by a protein kinase-like domain without catalytic activity. MLKL was originally discovered to be phosphorylated by receptor-interacting protein kinase 1/3, typically increase plasma membrane permeabilization, and disrupt the membrane integrity, ultimately executing necroptosis. Recent evidence uncovers the association of MLKL with diverse cellular organelles, including the mitochondrion, lysosome, endosome, endoplasmic reticulum, and nucleus. Thus, this review mainly focuses on the regulatory functions, mechanisms, and targets of MLKL in organelles rather than necroptosis and summarize the medical significance in multiple diseases. On this basis, we conclude and analyze the current progress and prospect for the development of MLKL-related drugs, from natural products, small-molecule chemical compounds, to proteolysis-targeting chimera. This review is aimed to propel the development of MLKL as a valid drug target and the discovery of novel MLKL-related drugs, and promote their further applications.